Chlorogenic Acid Promotes Autophagy and Alleviates Salmonella Typhimurium Infection Through the lncRNAGAS5/miR-23a/PTEN Axis and the p38 MAPK Pathway - Tan, Shirui; Yan, Fang; Li, Qingrong; Liang, Yaping; Yu, Junxu; Li, Zhenjun; He, Feifei; Li, Rongpeng; Li, Ming (Frontiers in Cell and Developmental Biology, 2020)
Background: Salmonella typhimurium (ST) causes several intestinal diseases. Polyphenols including chlorogenic acid (CGA) inhibit pathogenesis. Objective: This study aimed to investigate the mechanisms of CGA in ST infection. Methods: The intestinal pathological changes and survival rate of ST-infected mice were measured to verify the protection of CGA on ST infection. The antibacterial effects of CGA in vitro on the invasion to intestinal epithelial cells and autophagy was evaluated. The relationships among GAS5, miR-23a and PTEN were verified. Expression of inflammation- and autophagy-related proteins was detected. Results: CGA treatment alleviated pathological damage, improved the secretion disturbance of intestinal cytokines caused by ST infection, and reduced the mortality of mice. Intestinal GAS5 was upregulated after CGA treatment. LncRNA GAS5 competitively bound to miR-23a to upregulate PTEN and inhibit the p38 MAPK pathway. CGA regulated the p38 MAPK pathway through lncRNA GAS5/miR-23a/PTEN axis to promote autophagy in ST infection. The functional rescue experiments of miR-23a and PTEN further identified these effects. Conclusion: CGA promotes autophagy and inhibits ST infection through the GAS5/miR-23a/PTEN axis and the p38 MAPK pathway.